Formulation of initial flaw size for new crack growth under fatigue loading - Mohd Akramin, Mohd Romlay; Ahmad Syahrizan, Sulaiman; Rahman, M. M.; Mohd Ruzaimi, Mat Rejab; Al Emran, Ismail
Fatigue contributes to approximately 90% of failures for metallic structures. In order to model the behaviour of 3-dimensional fatigue crack growth, initial flaw size needs to be constructed in the finite element model. Small changes in value to the initial flaw size caused a great impact on the residual life of a cracked structure. The unknown initial flaw size is the main problem in analysis process since it will affects the remaining life of structures. Thus, it is essential to model the initial flaw size accurately. The main objective of this research is to formulate the initial flaw size in the structure through the calculation of stress intensity factor, surface crack growth and fatigue life prediction on the surface cracks. The formulation will be introduced in simulation code to model the unknown initial flaw size. The available initial flaw sizes from the experimental works are analysed using a statistical approach. Kolmogorov-Smirnov approach is used to verify the type of distribution. Based on the verified distribution, the initial flaw size is modelled in the numerical calculation. Subsequently, the numerical process produces raw mesh files with different initial flaw size. The finite element models with various initial flaw sizes are constructed and proceed with the calculation of the fatigue crack growth. The correlation and accuracy analysis for the initial flaw size model will be performed by comparing the stress intensity factors, surface crack growth and fatigue life prediction with the experimental results. The expected results of the research are the mathematical model of initial flaw size and a new formulation for fatigue crack growth to specialize for all finite element software and structural integrity assessment. It is expected to be the first 3D finite element analysis with initial flaw size modelling to be implemented in the oil and gas industries at Malaysia.